Acute Deep Vein Thrombosis in Venous Aneurysm following Closure of the Chronic Traumatic Arteriovenous Fistulae of the Lower Extremities - Saranat Orrapin; Supapong Arworn; Kittipan Rerkasem (Case Reports in Surgery)
Chronic traumatic arteriovenous fistula (AVF) commonly results from an unrecognized vascular injury. In this report, there were two cases of chronic traumatic AVF of the legs with a long history of stab (case 1) and shotgun wounds (case 2). Both cases presented with varicose veins together with hyperpigmentation around the ankle of the affected leg. Angiograms showed a single large AVF in case 1, whereas, in case 2, there was a single large AVF together with multiple small AVFs. In both cases large venous aneurysm was found next to a large AVF. An open surgical AVF closure for the large AVF was performed in case 1 successfully, but patient developed acute deep vein thrombosis (DVT) in a large venous aneurysm. In the second case, in order to prevent DVT, only closure of the large AVF was performed, which preserved arterial flow into the venous aneurysm. Case 2 did not have acute DVT. This report raised the concern about acute DVTs in venous aneurysms following the closure of chronic traumatic AVF in terms of prevention. Also chronic traumatic AVF is commonly due to misdiagnosis in the initial treatment, so complete and serial physical examinations in penetrating vascular injury patients are of paramount importance.